AQUAPONIK SOLUSI URBAN FARMING : AQUAPONIK SOLUSI URBAN FARMING DI PERUM PANDANWANGI GREEN MALANG - livia windiana; Nuriza Putri, Desiana; Amalia, Dina; Melliana Rahmah, Annisa' (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
Urban farming is one of the strategies that can shape family food security in urban areas. The aquaponic system is one of the urban farming activities. Small-scale aquaponics can be used for household scale. Maximum care is needed in aquaponic cultivation so that the growth and yield of vegetables and fish are good. Aquaponic can be an IRT solution that does not manage daily food expenditure by getting fish and vegetable crops that are harvested per day. The purpose of this community service is to: (1) analyze the frequency of household vegetable consumption, (2) analyze household income (savings) from the application of aquaponics. This study uses a qualitative approach and survey methods and uses income analysis. The results showed: (1) There was an increase in the frequency of eating vegetables in respondents by 9.5%. Before the socialization, the frequency of eating vegetables for households was 90.5%, while after the activity was carried out, the frequency of eating vegetables was 100%. Respondents consume vegetables every day so that they have fulfilled the minimum amount of vegetable and fruit consumption per household member is three portions of fruit and two portions of vegetables or vice versa every day (2) Household food income or saving by applying aquaculture is Rp. 126.000/month obtained from the harvest of vegetables and catfish.